PENERAPAN AKUNTANSI LINGKUNGAN TERHADAP BIAYA OPERASIONAL PENGELOLAAN LIMBAH PADA RSUD PROF. DR. M.A. HANAFIAH SM BATUSANGKAR - Yenti, Elfina; Candra, Revi; Juliati, Rahmi Asmara (IAIN Batusangkar, 2020)
This research aims to find out the application of environmental accounting to the emerging operational costs for waste management at Prof. RSUD. Dr. MA Hanafiah SM Hospital, Batusangkar. This research design was a qualitative descriptive by using Interview and documents as the techniques of collecting data. Then it was analyzed qualitatively by conducting several procedures like collecting data (documents, archives, and interview results), identifying environmental costs, proposing environmental costs budget, and writing the report of environmental costs. The results showed Prof. Dr. MA Hanafiah SM Hospital has not applied environmental accounting on its waste management. Although the hospital has good waste management, it is suggested to apply environmental accounting since it will be a reference at managing environmental costs, reporting specific and precise environmental costs, charging more accurate costs, and minimizing environmental costs.